Desenvolvimento de metodologia analítica para a determinação de arsênio em fertilizantes minerais - Machado, Raquel Cardoso (Universidade Federal de São Carlos, 2014)
Analytical method for the determination of As in samples of minerals fertilizers by Hydride Generation Flame Atomic Absorption Spectroscopy (HG AAS) was developed. First of all a study to check the effect of the concomitants on the analytical signal of the As was performed, and the presence of Cu and Ni, in the ratio analyte:interferent (1:10) and (1:1); Fe and Mg (1:500); Ca and Mn (1:50); Zn, Cr and Pb (1:5); and B (1:40) not interfere in the As analytical signal, with recovery within 97 and 103% in samples with the addition of these concomitants. Two procedures of digestion were optimized: using digester block with low pressure vials of PFA (perfluoroalkoxy) closed and cavity microwave oven. A full factorial design was used to investigate the variables (1) type of reagent (HNO3 7 mol L-1 + H2O2 (30% w w-1) or aqua regia), (2) time (only for digestion block) and (3) concentration of the reagents (diluted 1:1 or not). As answer the recovery of As, normalized between 0 and 1 using the function of desirability was utilized. The optimized conditions by using digester block with PFA vials were: HNO3 7 mol L-1 + H2O2 (30% w w-1), 4 h of digestion and diluted reagent 1:1. The best conditions for microwave digestion assisted were the same, with total time of 50 min. Concentrations of As also were determination by inductively coupled plasma optical emission spectrometry (ICP OES) to results comparison with the use of three different minerals fertilizers that were prepared from the use of the two optimized digestion procedures. The paired t-test was applied to compare the results and no statically difference were observed at 95% of confidence between the amount of As obtained in the sample preparation procedures, though differences between the techniques were observed. Therefore the digestion block can be considered an alternative procedure of minerals fertilizers sample preparation. The detection limit of the method defined as 3 s of background variation was 0.27 μg L-1, and 0.89 μg L-1 as limit of quantification. RSD for As determination at the concentration of 1 μg L-1 was 7.56%; for 7 μg L-1 was 2,28%; and for a solution of 20 μg L-1was 1.54%. Linear range was from1.0 up to 40.0 μg L-1, and 0.9926 of linearity were obtained. To accuracy evaluation, certificate reference material (NIST 695) was used, with recovery of 92 %. The method was successfully applied to the determination of As in nine samples of minerals fertilizers.
Development of analytical methods for determination of as in samples of minerals fertilizers
Keywords: Fertilizantes minerais; HGAAS; Preparação de amostra (Química analítica); CIENCIAS EXATAS E DA TERRA::QUIMICA